1985
DOI: 10.1111/j.1365-2125.1985.tb02673.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of mephenytoin p(4′)‐hydroxylation: difference between Orientals and Caucasians.

Abstract: The genetically controlled mephenytoin p(4′)‐hydroxylation capacity was determined in 118 Caucasians and 70 Orientals. After an oral dose of 50 or 100 mg of racemic mephenytoin, the amount of p(4′)‐ hydroxymephenytoin in 24 h urine was measured by gas chromatography. Bimodal distribution was found with 9/70 (13%) Orientals and 5/118 (4%) Caucasians demonstrating deficient p(4′)‐hydroxylation. The statistically significant difference between Orientals and Caucasians (P less than 0.05) was accounted for by the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(47 citation statements)
references
References 19 publications
3
42
0
1
Order By: Relevance
“…Compared with Caucasians where 40 to 50% are rapid acetylators, as much as 90% of the Japanese belong to the rapid acetylator phenotype (Sunahara et al, 1961). The frequency of PMs of mephenytoin wag reported to be 18% (Nakamura et al, 1985) and 22.6% (Jurima et al, 1985) in a Japanese population, whereas it was 2.7% in a white American (Nakamura et al, 1985) and 4.2% (Jurima et al, 1985) in a Canadian population. However, no PMs of debrisoquine were observed among the 100 Japanese subjects studied by Nakamura et al (1985).…”
Section: Discussionmentioning
confidence: 92%
“…Compared with Caucasians where 40 to 50% are rapid acetylators, as much as 90% of the Japanese belong to the rapid acetylator phenotype (Sunahara et al, 1961). The frequency of PMs of mephenytoin wag reported to be 18% (Nakamura et al, 1985) and 22.6% (Jurima et al, 1985) in a Japanese population, whereas it was 2.7% in a white American (Nakamura et al, 1985) and 4.2% (Jurima et al, 1985) in a Canadian population. However, no PMs of debrisoquine were observed among the 100 Japanese subjects studied by Nakamura et al (1985).…”
Section: Discussionmentioning
confidence: 92%
“…They are PMs according to either of the criteria normally used (Horai et al, 1989;Jurima et al, 1985;Kupfer & Preisig, 1984). The remaining eight subjects (seven were EMs and one was a PM had only minor complaints (e.g., dizziness) after the mephenytoin dose.…”
Section: Gerontokinetics -A Replymentioning
confidence: 99%
“…Mephenytoin has low affinity for CYP2C19 (K m values ranging from 59 -143 M) (Jurima et al, 1985), and its CYP2C19-dependent metabolic ratio has been shown to change with long-term storage of samples (Zhang et al, 1991;Tamminga et al, 2001), whereas the formation of 5-hydroxyomeprazole from omeprazole has been shown to be mediated by CYP2C19 as well as CYP3A4 (Andersson et al, 1993). In vivo studies will be needed to determine whether 18-MC can be used as an in vivo CYP2C19 probe substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The poor metabolizer (PM) phenotype, constituting those homozygous for inactive alleles and therefore having no CYP2C19 activity, occurs with a frequency of 2.5 to 6% in Caucasians. Higher frequencies are observed in Chinese (15-17%) and Japanese (18 -23%) populations (Inaba et al, 1984;Wedlund et al, 1984;Jurima et al, 1985;Nakamura et al, 1985;Horai et al, 1989;Bertilsson et al, 1992). PMs may be more likely to experience adverse drug effects due to increased plasma concentration and/or increased half-life of the parent drug.…”
mentioning
confidence: 99%